2021
DOI: 10.1186/s12906-021-03447-3
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-rich extract of Ocimum gratissimum leaves prevented toxic effects of cyclophosphamide on the kidney function of Wistar rats

Abstract: Background Cyclophosphamide (CP) is one of the potent and low cost chemotherapy used in clinical setting against a variety of tumors. However, its association with nephrotoxicity limits its therapeutic use. Ocimum gratissimum leaf is a medicinal plant with numerous pharmacological and therapeutic efficacies, such as antioxidant, anti-inflammation, and anti-apoptotic properties. Methods The present study was designed to evaluate the protective effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…The induction of oxidative stress was confirmed by increased MDA level in this study. Our results are consistent with the published findings from systematic investigations showing CYP-induced depression of antioxidant apparatus and augmentation of lipid peroxidation in the liver, kidney and heart 4 15 23 . Interestingly, the STG protects the systemic antioxidant defences as indicated by the significant restoration of SOD, CAT, and GPx activities and level of GSH comparable to normal control.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The induction of oxidative stress was confirmed by increased MDA level in this study. Our results are consistent with the published findings from systematic investigations showing CYP-induced depression of antioxidant apparatus and augmentation of lipid peroxidation in the liver, kidney and heart 4 15 23 . Interestingly, the STG protects the systemic antioxidant defences as indicated by the significant restoration of SOD, CAT, and GPx activities and level of GSH comparable to normal control.…”
Section: Discussionsupporting
confidence: 93%
“…More interestingly, the markers of renal and cardiac damage were also altered indicating CYP-induced cardiorenal injury in this study. However, studies have shown that CYP could damage the heart 23 , kidney 4 5 , testis 6 24 , and bladder 3 . In this study, CYP prominently increased levels of urea, creatinine as well as activities of cardiac CK and LDH ( Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations